2011
DOI: 10.1007/s12098-011-0515-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum Fructosamine and Retinopathy of Prematurity

Abstract: Although the duration of hyperglycemia may contribute to the development of retinopathy of prematurity, serum corrected fructosamine does not have a good predictive value in developing retinopathy of prematurity in very-low-birth-weight (VLBW) infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Some studies have documented alterations in ocular growth and changes in refractive errors in infants with ROP (9) . It is widely recognized that ROP is a multi-factorial condition, with gestational age, low birth weight, blood transfusion, oxygen exposure, intraventricular haemorrhage, and necrotizing enterocolitis all implicated in the disorder (10,11) . The aim of the present study was to determine the horizontal corneal diameter, central corneal thickness, and axial length in premature infants.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have documented alterations in ocular growth and changes in refractive errors in infants with ROP (9) . It is widely recognized that ROP is a multi-factorial condition, with gestational age, low birth weight, blood transfusion, oxygen exposure, intraventricular haemorrhage, and necrotizing enterocolitis all implicated in the disorder (10,11) . The aim of the present study was to determine the horizontal corneal diameter, central corneal thickness, and axial length in premature infants.…”
Section: Introductionmentioning
confidence: 99%
“…Seven out of the 9 studies provided primary data on the number of subjects with hyperglycemia and without hyperglycemia in both the ROP and non-ROP groups21222324252627. Pooling up data from these 7 studies showed that hyperglycemia is associated with ROP with an unadjusted OR of 4.16 (95% CI: 2.09–8.29, I 2 = 65%, P <0.0001) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…It is concluded that "serum corrected fructosamine does not have a good predictive value in developing retinopathy of prematurity in verylow-birth-weight (VLBW) infants [1]." A concern is on the measurement of serum fructosamine in this work.…”
mentioning
confidence: 97%
“…Sir, The recent publication on serum fructosamine and retinopathy is very interesting [1]. It is concluded that "serum corrected fructosamine does not have a good predictive value in developing retinopathy of prematurity in verylow-birth-weight (VLBW) infants [1]."…”
mentioning
confidence: 99%
See 1 more Smart Citation